Sistem Prediksi Mutu Air Di Perusahaan Daerah Air Minum Tirta Raharja Menggunakan K – Nearest Neighbors (K – NN) - Rahandanu Rachmat; Yulison Herry Chrisnanto; Fajri Rakhmat Umbara (Ikatan Ahli Informatika Indonesia, 2020)
PDAM (Perusahaan Daerah Air Minum) Tirta Raharja is the only Regional Business Entity (BUMD) that has the task of providing clean water services to the people of Cimahi City. Clean water is the main requirement that must be consumed by the community and managed in the smooth running of community activities. The development of the city of Cimahi is currently quite fast, with plans to build smart cities, causing the need for clean air as needed. K - Nearest Neighbor (KNN) is a classification algorithm that considers several supporting parameters to carry out a classification process that results in ease of calculation and power. KNN can be considered as one of the most famous non-parametric models. In the research and implementation process of data mining in the regulation of water quality feasibility in PDAM Tirta Raharja using K - the nearest neighbor can be denied as the K - the nearest neighbor implemented in the process of testing the drinking water feasibility in PDAM Tirta Raharja, can be used 93% to be used with the Eligible label Drunk, and 98% for accuracy testing with the label Not Eligible to drink with a K value of 14 where the K value is the most ideal amount that must go through K - Fold Validation Validation of a total of 1,818 data.